RESPONS BERBAGAI JENIS TANAMAN PADI (Oryza sativa L.) TERHADAP METODE SRI (System of Rice Intensification) DI LAHAN DARAT - Suryaman Birnadi (JURNAL ISTEK, 2013)
An experiment was conducted to study growth and yield two cultivars of rice with organic fertilizer bokashi and farmyard manure on SRI (System of Rice Intensification). Result showed there are no interaction effect between the application of organic fertilizer and cultivars. Although there is significant effect an main effect of growth and yield. Soil+bokashi proveed to be the highest effect on plant height, or number vegetative, dry plant weight, weight of dry harvest grain rice NPK absorption, and the mean growth rate. Soil+ farmyard manure proved to be the highest effect an weight of dry harvest grain rice. Cv. Ciherang proveed to be the highest effect on plant height, on number vegetative, dry plant weight, and the mean growth rate.